DNA methylation in esophageal cancer: technological advances and early detection clinical applications - Tang, Jiyu; Shi, Xiaoming; Song, Chao; Zhang, Wenjing; Yan, Yan; Dai, Linchao; Wu, Di; Qiu, Jie; Liu, Jiahuan; Wang, Tao; Lu, Zuhong (Frontiers in Oncology, 2025)
Esophageal cancer (EC) is a malignant tumor with high mortality rates, where early screening and diagnosis are critical for improving patient outcomes. DNA methylation, a key epigenetic modification, has emerged as a significant biomarker for early detection of EC. The advancement in DNA methylation sequencing technologies, including first-generation and next-generation sequencing (NGS), has revolutionized the way we identify and analyze these biomarkers. First-generation sequencing, has been instrumental in identifying specific methylation sites. However, its limited throughput renders it impractical for large-scale screening of multiple samples. In contrast, NGS offers high-throughput capabilities, allowing for the simultaneous analysis of thousands of DNA fragments. NGS significantly enhances the efficiency and accuracy of DNA methylation profiling, permitting genome-wide identification of multiple methylation markers. This approach offers a promising avenue for the enhanced early detection of EC by providing a comprehensive view of the methylation landscape. The integration of NGS into clinical practice is capable of transforming EC screening by offering heightened sensitive and specific approach to identifying patients at risk. As our comprehension of the role of DNA methylation in cancer progression deepens, the development of targeted therapies based on methylation profiles may also become a reality. In conclusion, the evolution of DNA methylation sequencing technologies has unlocked new avenues for the early EC detection. While first-generation sequencing has laid the groundwork for characterizing specific methylation events, NGS has expanded the scope of screening, offering a more robust and scalable solution for identifying early-stage EC.